2004
DOI: 10.1111/j.1532-5415.2005.53004.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Control Mediates Memory's Association with Change in Instrumental Activities of Daily Living: The Freedom House Study

Abstract: ECF is a strong, significant, and independent correlate of functional status in normal aging. In contrast, decline in memory, as measured using the CVLT, has no independent association with the rate of change in functional status. This suggests that amnestic mild cognitive impairment can be associated with dementia only though the subsequent or comorbid development of ECF impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 37 publications
14
102
1
2
Order By: Relevance
“…If so, failing executive abilities would then reduce compensatory ability and compound the loss of everyday function. Consistent with the present data, Royall and colleagues (Royall et al, 2005) found that change in executive function, but not change in memory, was associated with change in functional impairment over time, also suggesting that executive dysfunction may be particularly important to longitudinal declines in everyday function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…If so, failing executive abilities would then reduce compensatory ability and compound the loss of everyday function. Consistent with the present data, Royall and colleagues (Royall et al, 2005) found that change in executive function, but not change in memory, was associated with change in functional impairment over time, also suggesting that executive dysfunction may be particularly important to longitudinal declines in everyday function.…”
Section: Discussionsupporting
confidence: 90%
“…First, executive dysfunction may play a particularly important role in the progression of disability. For example, Royall (Royall, 2006;Royall et al, 2004, Royall et al,2005 argues for the central role of executive dysfunction in causing functional disability and in the conversion of MCI to dementia. Perhaps executive functions, because of their role in regulating and coordinating other mental functions, organizing behavior and generating responses, play a central role in a variety of everyday activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of executive function in the performance of IADL [16,31,32]. In our study, TMT-B was correlated with IADL and the 3 executive subscales.…”
Section: Discussionsupporting
confidence: 67%
“…Se ha descrito que el deterioro cognoscitivo con cambios en el control de las funciones ejecutivas es suficiente para explicar el deterioro funcional general, y que las personas con deterioro cognoscitivo amnésico tienen menor riesgo de llegar a la demencia que las que presentan problemas en el control de funciones ejecutivas (46,47). En un estudio realizado por Royall y colaboradores se describe que los cambios en el control de las funciones ejecutivas están relacionadas con las actividades instrumentales de la vida diaria y, por lo tanto, con el deterioro de la capacidad funcional (48).…”
Section: Cuadro 2 Estado De Salud De Los Adultos Mayores Estudiadosunclassified